Grand Duke Sergey Alexandrovich and the Development of Religious and Educational Activities in the Vyatka Province in the Late XIX - Early XX Centuries - E. N. Nemchaninova; M. Yu. Polovnikova (Научный диалог)
Based on archival materials and published sources, the article examines the activities of Grand Duke Sergei Alexandrovich as one of the zealous patrons of the Russian Orthodox Church. It is indicated that the Grand Duke was the chairman of numerous societies, including the Imperial Orthodox Palestinian Society, engaged in religious, educational and scientific activities in the Middle East, and sought to provide public support in the territory of the Russian Empire. Particular attention is paid to the development of the network of departments of the Orthodox Palestinian Society since 1894, after the opening of which in the territory of the Russian Empire, Grand Duke Sergei Alexandrovich became their patron. It is reported that in the Vyatka province, the Vyatka department of the Imperial Orthodox Palestinian Society was opened, also under the patronage of the Grand Duke. The authors described the degree of participation of the Grand Duke in the activities of the Vyatka Division of the Imperial Orthodox Palestinian Society and the main interests of the patron in terms of the development of the department. Attention is paid to the activities of Grand Duke Sergei Alexandrovich as the patron saint of another organization of the Vyatka eparchy - the Vyatka fraternity of St. Nicholas the Wonderworker. It is concluded that the patronage of the Grand Duke Sergei Alexandrovich, although it was largely nominal - edifying - in nature but played an important role in the development and strengthening of local organizations of the Vyatka eparchy.